Catalytic Performance of Commercial Zeolites Y as Catalyst for Ethylene Production from Ethanol Dehydration - Soh, Jiah Chee; Chong, Soo Ling; Chin, S. Y.; Cheng, C. K. (Dept. of Chemistry, UTM, 2017)
Catalytic dehydration of ethanol into ethylene was studied over commercial Zeolites-Y with different Si:Al ratios between 5.1:1 and 80:1, and temperature from 573 K to 773 K. The physicochemical properties of fresh and spent catalyst of Zeolite Y Si:Al 80:1 (best performing catalyst) were investigated using N2-physisorption, TGA, SEM-EDX, NH3-TPD, FTIR and XRD. Results showed that catalysts with higher Si:Al ratios exhibit better catalytic performance in terms of higher ethanol conversion and higher selectivity to ethylene. Indeed, zeolites-Y with Si:Al ratio 5.1:1 and 12:1 demonstrated low catalytic activity with ethanol conversion of 34% and 2%, respectively. However, ethylene selectivity of NH3-Y (5) was 84%, which was considerably higher than NH3-Y (12) which was 26%, indicated that this catalyst was not promoting the formation of other hydrocarbons i.e. methane and ethane. Albeit all of the catalysts namely H-Y (30), H-Y (60) and H-Y (80) showed favorable performance in ethanol dehydration, H-Y (80) attained almost total selectivity to ethylene and highest conversion of 73.0% among all the tested catalysts.